(untitled) (International Journal of Management (IJM), 2023)
The purpose of the present study is to explore the impacts of social media and social media usage on anxiety among the youth. A total of 269 students from the city Pune participated in this research survey. To interpret and collect the data, Version 28 of software SPSS was used. To analyze the data in depth, methods like Regression Analysis and Pearson Correlation were used. The findings of the study interpreted that social media has an impact on anxiety of the students. Anxiety has a positive correlation with social media and social media usage.